2008
DOI: 10.1089/end.2008.0357
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect of a Potent Antioxidant, Pomegranate Juice, in the Kidney of Rats with Nephrolithiasis Induced by Ethylene Glycol

Abstract: This experiment shows the protective effect of PJ in the EG-induced crystal depositions in renal tubules.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(39 citation statements)
references
References 31 publications
2
33
0
Order By: Relevance
“…The protective role of nitric oxide (NO) in different models of renal failure has been documented [136], including glycerol-induced renal failure [137] and nephrolithiasis induced by ethylene glycol [138]. These studies have demonstrated that levels of NO are decreased in glycerol-induced renal failure and different agents have shown to produce renoprotection by increasing the NO production [120].…”
Section: Pomegranate (Punica Granatum L)mentioning
confidence: 99%
“…The protective role of nitric oxide (NO) in different models of renal failure has been documented [136], including glycerol-induced renal failure [137] and nephrolithiasis induced by ethylene glycol [138]. These studies have demonstrated that levels of NO are decreased in glycerol-induced renal failure and different agents have shown to produce renoprotection by increasing the NO production [120].…”
Section: Pomegranate (Punica Granatum L)mentioning
confidence: 99%
“…Pectinase hydrolyzes the -1,4-galacturonide bonds in pecti, improves the extraction and Wltration process, and prevents the formation of pectin gels. The extract was Wltered, pasteurized, concentrated, and stored at ¡18°C, as described previously [21,22]. Concentrated PE was diluted in water (20 mL concentrated extract/500 mL of distilled water).…”
Section: Drugsmentioning
confidence: 99%
“…Known as "the fruit of the dead" in ancient Greek mythology [18], pomegranates have been used to treat inXammatory disease for centuries, reportedly have cholesterol-lowering properties, and prevent atherogenesis and urolithiasis [19][20][21]. Pomegranate fruit is rich in polyphenol antioxidants, including tannins and anthocyanins [12,22].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have demonstrated oxidant stress in experimental urolithiatic rats would promote the synthesis and release of NO and caused the elevation of MDA secondarily. Meanwhile, activated antioxidant system upregulated SOD activities to scavenge free radical in early stage, but in late stage excessive oxidative stress decreased antioxidant enzyme activities [7,43,44]. Therefore, NO, MDA and SOD as the good indicators are widely used to estimate oxidant-antioxidant status both in vitro and in vivo.…”
Section: Discussionmentioning
confidence: 99%